Occurrence of non-O157 shiga toxin-encoding Escherichia coli in artisanal mozzarella cheese in Brazil: Risk factor associated with food workers - Cardoso, Patricia [UNESP]; Marin, José Moacir (FapUNIFESP (SciELO), 2017)
Mozzarella cheese is considered a safe food due to the high temperature treatment used in the traditional process of stretching into hot water; however, a post-process contamination during the cheese manufacture or during the processing (before distribution) could occur. This study investigated the occurrence of Shiga toxin-encoding Escherichia coli (STEC) strains in homemade‑mozzarella cheese. In total, 59 raw milk cheese samples collected at a local producer in the Jequitinhonha Valley (Northeast of Minas Gerais, Brazil) were submitted for microbiological analysis, and 38 (64.4%) tested positive for E. coli. Then, 147 strains of E. coli were isolated from positive samples and screened by polymerase chain reaction for the presence of the genes encoding the following virulence factors: stx1 and stx2 (verotoxin types 1 and 2) and eae (intimin). All the isolates were negative for the stx 2, 14 isolates (9.5%) were positive for the stx1 gene, and 11 of them also harbored the eae gene. A food worker was probably involved in cheese contamination during the manufacture schedule. While the development of STEC infection in humans is not completely understood, all STEC- contaminated food can be considered potentially hazardous.
Keywords: Escherichia coli; Food handler contamination; Homemade cheese; Virulence genes